Negative emotion accumulation and personal motivation - Staner, Clément (AWI discussion paper series, 2024)
Understanding how emotions stemming from negative outcomes affect investment decisions is critical for studying choice under uncertainty. I build a framework to study how past and anticipated negative emotions interact with an agent’s preference and environment to influence her investment level. I show that the dynamic effect of emotions on decisions is more complicated than previously thought and requires a careful analysis of the decision environment to build correct predictions. Using baseball data, I show how to use the theoretical framework empirically to investigate the dynamic impact of emotion and find that it leads to suboptimal pitch velocity decisions.